Working Capital Management and Performance of Retail Businesses in Iganga Market, Iganga Municipality, Iganga District - Julius Isaac Wanjoli (Uganda Christian University, 2026)
Effective working capital management is crucial for financial sustainability and Performance of retail business. This study examines working capital management and performance of retail businesses in Iganga Market, Iganga Municipality. Specifically, it explores how cash management, inventory management and accounts receivable management influence business performance. The study adopts a mixed-method approach incorporating semi- structured interview and surveys to gather data from Vendors. The findings aim to provide insights into best practices for optimizing working capital to enhance performance. This research will contribute to existing body of knowledge and offer practical recommendation for business owners in the retail sector.
Undergraduate